Characterization and Proposed Nomenclature of Epidemic Strains of MRSA in Canada - AE Simor; D Boyd; L Louie; A McGeer; M Mulvey; BM Willey; the Canadian Hospital Epidemiology Committee; the Canadian Nosocomial Infection Surveillance Program (Canadian Journal of Infectious Diseases)
The incidence of methicillin-resistant Staphylococcus aureus (MRSA) has been increasing in many Canadian hospitals over the past few years. Some strains may be considered ‘epidemic’, in that they are clinically or epidemiologically significant, and have been identified in patients from multiple hospitals and geographic regions across the country. This paper describes phenotypic and genotypic characteristics of four epidemic MRSA strains in Canada and proposes standardized nomenclature.